2009
DOI: 10.1080/08958370802524373
|View full text |Cite
|
Sign up to set email alerts
|

Anin vitrostudy of the effect of size and timing of administration of titanium dioxide particles on antigen presenting activity of alveolar macrophages and peripheral blood monocytes

Abstract: Previous studies have shown that inhaled particles exacerbate asthma and allergic rhinitis. Several factors related to the particle may play a role in immune-stimulating activity; however, the underlying mechanisms remain unclear. We carried out in vitro studies to investigate the effects of TiO(2) particle exposure on antigen presenting activity and expression of the associated cell-surface molecules (Ia, B7.1, B7.2) in rat derived monocytes and alveolar macrophages, in terms of two aspects of the particles: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Several in vitro studies also provide further information regarding the direct effects of TiO 2 nanoparticles on immune cells. Munidasa et al reported that TiO 2 nanoparticles showed greater influence on the antigen presenting activity of monocytes and alveolar macrophages [30]. In addition, Moon et al showed a reduction in lymphocyte proliferation induced by lipopolysaccharide (LPS) or concanavalin A (Con A) upon exposure to TiO 2 nanoparticles [29].…”
Section: Studies Concerning Nano-scaled Titanium Dioxide Particlesmentioning
confidence: 99%
“…Several in vitro studies also provide further information regarding the direct effects of TiO 2 nanoparticles on immune cells. Munidasa et al reported that TiO 2 nanoparticles showed greater influence on the antigen presenting activity of monocytes and alveolar macrophages [30]. In addition, Moon et al showed a reduction in lymphocyte proliferation induced by lipopolysaccharide (LPS) or concanavalin A (Con A) upon exposure to TiO 2 nanoparticles [29].…”
Section: Studies Concerning Nano-scaled Titanium Dioxide Particlesmentioning
confidence: 99%
“…The degree of activation has been further correlated to properties including size, surface modification, crystallinity, and morphology (527,538,1042,1050,1051). Several studies have also reported increases in many of the same markers on DC isolated from animals exposed to metal nanomaterials in vivo (773,844,1052).…”
Section: Metal Nanomaterials Effects On DC and Sensitization In Vitromentioning
confidence: 98%
“…Some metal nanomaterials have been shown to enhance antigen-presenting behaviors of pulmonary macrophages, an effect which could also promote sensitization by generating an additional population of cells capable of stimulating adaptive immune cells. FeNP and TiO2NP have been shown to increase expression levels of several activation markers by pulmonary macrophages that indicate enhanced antigen presenting capacity (773,844). Several metal nanomaterials have also been shown to alter macrophage chemotactic ability, which may further impact their potential to act as APC in the lungs (845).…”
Section: Evidence For Increased Potential For Respiratory Sensitizatimentioning
confidence: 99%
See 1 more Smart Citation